Design of a Novel Hybrid Control Strategy for ES Grid-Connected Inverter for Smooth Microgrid Transition Operation - Feng Zheng (IEEE Access, 2019)
A novel hybrid control strategy for energy storage (ES) is applied in accordance to the recommendations by the IEEE Std. 1676. The strategy mainly consists of the model predictive controller (MPC), two-degree of freedom algorithm and modified droop control. In inverter control layer, MPC and two-degree of freedom algorithm are adopted to construct a generalized controller to enable ES operate in microgrid grid-connected and islanded operation modes with a single control structure, motivating the smooth transition between microgrid operating modes. And MPC and two-degree of freedom algorithm are used in the control layer's current inner loop and voltage outer loop, respectively. Comparing with the traditional double loop control from the perspective of structure, with the novel strategy the control layer's current inner loop is without pulse width modulation (PWM) and only a single proportional-integral (PI) controller is applied in its voltage outer loop, so that ES's robust performance can be enhanced. And because of the high frequency inverter's equivalent transfer function with the smaller time constant, MPC's transfer function approximated as being unitary. Therefore, when the two-degree of freedom algorithm construct the inverse model for the controlled object in control layer's voltage outer loop, from the application layer perspective, the control layer can be recognized as unity gain. Thus, the control layer's harmful disturbances associated with the operation mode transitions can be removed. In the application layer, through adding decoupling inductance and introducing microgrid's voltage and angular frequency feedforward compensations to carry out PQ and modified droop controls, the grid-connected and island control targets of ES application layer can be realized. In particular, when microgrid operation mode is switched to island, with the help of modified droop control, microgrid's voltage and frequency can be quickly restored to standard values. Through the theoretical derivation and simulation results, it can be proved that under microgrid's plan or non-plan operation mode switching, the proposed method can not only can not only implement the microgrid smooth switching, but also strengthen its transient performance.